Multiple persistent organic pollutants in mothers' breastmilk: Implications for infant dietary exposure and maternal thyroid hormone homeostasis in Uganda, East Africa - Matovu, Henry; Li, Zhong-Min; Henkelmann, Bernhard; Bernhöft, Silke; De Angelis, Meri; Schramm, Karl-Werner; Sillanpää, Mika; Drago Kato, Charles; Ssebugere, Patrick (Science of The Total Environmen, 2021)
Persistent organic pollutants (POPs) are ubiquitous contaminants with adverse health effects in the ecosystem. One of such effects is endocrine disruption in humans and wildlife even at background exposure concentrations. This study assessed maternal breastmilk concentrations of POPs; brominated flame retardants (BFRs), polychlorinated biphenyls (PCBs) and polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs), and the potential health risks posed to the nursing infants. We also evaluated the association of these POPs with total 3,3′,5- triiodo-L-thyronine (T3), L-thyroxine (T4), and 3,3′,5′-triiodo-L-thyronine (rT3) levelsmeasured in human breast milk. Thirty breastmilk samples were collected from Kampala, Uganda between August and December 2018. Hexabromobenzene was not detected while the maximum level of 2,2′,4,4′,5,5′-hexabrombiphenyl was 64.7 pg/g lw. The median levels of total indicator PCBs, PBDEs, dioxin-like PCBs, and PCDD/Fs in the samples were 159 pg/g lw, 511 pg/g lw, 1.16 pg TEQ/g lw, and 0.4 pg TEQ/g lw, respectively. These levels were lower than those reported in other countries. Owing to their bio accumulative nature, PCBs −81, −169, andΣPCDD/Fs increased with increase in maternal age. Estimated dietary intakes for dioxin-like PCBs and PCDD/Fs were lower than those reported elsewhere but were higher than the WHO tolerable daily intakes suggesting potential health risks to nursing infants. In adjusted single pollutant models, PCB-126, PCB-169, andΣPCBTEQ were negatively associated with T3, while 1,2,3,4,5,7,8-HpCDF was positively associated with rT3. Although these associations did not persist in multi pollutant models, our findings suggest potential thyroid hormone disruption by POPs in mothers. This may reduce the levels of thyroid hormones transferred from the mother to the neonates and, hence, adversely influence infant growth. A temporal study with a bigger sample size is required to corroborate these findings
Keywords: Persistent organic pollutants; Breastmilk; Dietary exposure; Thyroid hormones; Africa